Interaction of Oxazaphosphorines with Multidrug Resistance-Associated Protein 4 (MRP4) - Zhang, Jing (Springer US, 2010)
Multidrug resistance-associated protein 4 (MRP4) is an organic anion efflux pump capable of transporting nucleoside, nucleotide analogs, and cyclic nucleotide. MRP4 could have an influence on the resistance and transport of the two oxazaphosphorines, cyclophosphamide (CP) and ifosfamide (IF). V/HepG2 (HepG2, hepatoma cells stably transfected with an empty vehicle plasmid) and MRP4/HepG2 (HepG2 cells stably expressing MRP4) were exposed to CP and IF in the absence or presence of various MRP4 inhibitors. HepG2 and HEK293 human kidney cells were also used to investigate the inducing potency of oxazaphosphorines on the MRP4 expression. In this study, insertion of MRP4 gene in HepG2 cells was found to confer significant resistance to CP and IF in the 48-h drug-exposure assays. In the presence of various MRP4 inhibitors, the resistance to CP and IF was then partially reversed. These indicate that CP and IF are highly possible substrates of MRP4. In addition, CP and clofibrate (CFB), a reported MRP4 inducer, in vivo significantly increased the MRP4 expression at both protein level and mRNA level in HEK293 cells at higher concentrations, while IF significantly decreased the MRP4 expression at mRNA level at lower concentration and had no effect at higher concentrations. However, all tested compounds (CP, IF, and CFB) did not change the MRP4 protein expression in HepG2 cells. CP and CFB are cell-specific and concentration-dependent MRP4 inducers. The finding may have implications in the CP- or IF-based chemotherapy.